Practice 2

The terms 3r^{2} and 4t are unlike, so this expression cannot be simplified. Substitute 3 for r and –2 for t:
3(3)2 + 4(–2) = 3(9) –8 = 27 – 8 = 19

This expression has two r terms and two t terms.
Combine the r terms: –r + 9r = 8r.
Combine the t terms: 5t – 2t = 3t.
The expression is now 8r + 3t.
Substitute 3 for r and –2 for t:
8(3) + 3(–2) = 24 –6 = 18

This expression has two r terms, one t term, and one t^{2} term.
Combine the r terms: 6r –2r = 4r.
The expression is now 4r –3t^{2} + 4t.
Substitute 3 for r and –2 for t:
4(3) –3(–2)^{2} + 4(–2) = 4(3) –3(4) –8 = 12 –12 –8 = –8

Use the distributive law to find –2r(8 + t). Multiply –2r by 8 and multiply –2r by t: –2r(8 + t) = –16r + –2rt
This expression, 4rt –16r –2rt, has one r term and two rt terms.
Combine the rt terms: 4rt –2rt = 2rt.
The expression is now 2rt –16r.
Substitute 3 for r and –2 for t:
2(3)(–2) –16(3) = 6(–2) –48 = –12 –48 = –60

This expression has two a terms, two b terms, and one c term.
Combine the a terms: 2a –5a = –3a.
Combine the b terms: 3b –4b = –b.
The expression is now –3a –b –4c.
Substitute –3 for a, 6 for b, and 1 for c:
–3(–3) –(6) –4(1) = 9 –6 –4 = 3 –4 = –1

Use the distributive law to find 4(a –b + 2c).
Multiply each term in parentheses by 4:
4(a –b + 2c) = 4a –4b + 8c
Use the distributive law again to find c(a –3). Multiply both terms in parentheses by c:
c(a –3) = ac –3c
This expression, 4a –4b + 8c + ac –3c, has one a term, one b term, two c terms, and one ac term.
Combine the c terms: 8c –3c = 5c.
The expression is now 4a –4b + 5c + ac.
Substitute –3 for a, 6 for b, and 1 for c:
4(–3) –4(6) + 5(1) + (–3)(1) = –12 –24 + 5 –3 = –36 + 5 –3 = –31 –3 = –34

Use the distributive law to find b(3a + c). Multiply each term in parentheses by b:
b(3a +c) = 3ab + bc
This expression, 3c^{2} –3ab + 3ab + bc, has one c^{2} term, two ab terms, and one bc term.
Combine the ab terms: –3ab + 3ab = 0.
The expression is now 3c^{2} + bc.
Substitute 6 for b and 1 for c:
3(1)2 + (6)(1) = 3(1) + (6)(1) = 3 + 6 = 9 
Use the distributive law to find 2b(c –a). Multiply each term in parentheses by 2b:
2b(c –a) = 2bc –2ab
This expression, 5b + 2bc –2ab + 3ab, has one b term, one bc term, and two ab terms.
Combine the ab terms: –2ab + 3ab = ab.
The expression is now 5b + 2bc + ab.
Substitute –3 for a, 6 for b, and 1 for c:
5(6) + 2(6)(1) + (–3)(6) = 30 + 12(1) –18 = 30 + 12 –18 = 42 –18 = 24

Use the distributive law to find 6(3w + x). Multiply both terms in parentheses by 6:
6(3w + x) = 18w + 6x
Use the distributive law again to find –3(w –z). Multiply both terms in parentheses by –3:
–3(w –z) = –3w + 3z
This expression, 18w + 6x + 2y –3w + 3z, has two w terms, one x term, one y term, and one z term.
Combine the w terms: 18w –3w = 15w.
The expression is now 15w + 6x + 2y + 3z.
Substitute 1 for w, –2 for x, 3 for y, and –4 for z:
15(1) + 6(–2) + 2(3) + 3(–4) = 15 –12 + 6 –12 = 3 + 6 –12 = 9 –12 = –3

Use the distributive law to find 5(z + 4). Multiply both terms in parentheses by 5:
5(z + 4) = 5z + 20
Use the distributive law again to find –10(12z + y). Multiply both terms in parentheses by –10:
This expression, w^{2} –3x + 5z + 20 –5z –10y, has one w^{2} term, one x term, one y term, two z terms, and one constant.
Substitute 1 for w, –2 for x, and 3 for y:
(1)^{2} –3(–2) + 20 –10(3) = 1 + 6 + 20 –30 = 7 + 20 –30 = 27 –30 = –3
 1

2
Ask a Question
Have questions about this article or topic? AskRelated Questions
See More QuestionsPopular Articles
 Kindergarten Sight Words List
 First Grade Sight Words List
 10 Fun Activities for Children with Autism
 Grammar Lesson: Complete and Simple Predicates
 Definitions of Social Studies
 Child Development Theories
 Signs Your Child Might Have Asperger's Syndrome
 How to Practice Preschool Letter and Name Writing
 Social Cognitive Theory
 Theories of Learning